Activity of Supra (E)-Dependent Dehydrogenases of Staphylococcus epidermidis Strains Susceptible to Cefotaxime - O. A. Kolenchukova; A. A. Savchenko (Антибиотики и Химиотерапия)
Investigation of the activity of supra- and supra (e)-dependent dehydrogenases of the Staphylococcus epidermidis strains isolated from the pharynx mucous membrane of healthy subjects showed that the level of the substrate exchange between the tricarbonic acid cycle and the amino acid metabolism reactions, as well as the intensity of the glycolysis terminal reactions and the glutathione reductase activity depended on the bacteria susceptibility to cefotaxime.